Soziale Netzwerke Und Gesundheitliche Ungleichheiten 2019
DOI: 10.1007/978-3-658-21659-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Geschlecht und gesundheitliche Ungleichheiten – Soziale Netzwerke im Kontext von Gesundheit und Gesundheitsverhalten

Abstract: • Es gibt deutliche Unterschiede hinsichtlich der Morbidität (Krankheitshäufigkeit) und der Mortalität (Sterblichkeit) zwischen Männern* 1 und Frauen*.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Bereavement, especially widowhood, is common in old age and can be accompanied by serious health consequences [ 5 , 6 ]. Previous studies have emphasized the impact of widowhood on depression in old age [ 2 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bereavement, especially widowhood, is common in old age and can be accompanied by serious health consequences [ 5 , 6 ]. Previous studies have emphasized the impact of widowhood on depression in old age [ 2 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the gender category influences numerous areas of social life and, according to Gamper et al [15], plays a significant role as a category of social order and social positioning [5,43]. In the area of health, numerous studies have shown a strong difference between the sexes (morbidity, mortality, development and course of diseases, health behaviour) [28,42].…”
Section: Introductionmentioning
confidence: 99%
“…In the area of health, numerous studies have shown a strong difference between the sexes (morbidity, mortality, development and course of diseases, health behaviour) [28,42]. Furthermore, social and cultural factors have an impact on health care and are expressed in partly significant gender differences [15,28].…”
Section: Introductionmentioning
confidence: 99%